Creatine supplementation in young soccer players - Ostojic, S. M. (Canadian Journal of Applied Physiology, 2002)
The purpose of this study was to examine the effects of acute creatine-monohydrate supplementation on soccer-specific performance in young soccer players. Twenty young male soccer players (16.6 ± 1.9 years) participated in the study and were matched and allocated to 2 randomly assigned trials: ingesting creatine-monohydrate supplement (3 × 10-g doses) or placebo for 7 days. Before and after the supplementation protocol, each subject underwent a series of soccer-specific skill tests: dribble test, sprint-power test, endurance test, and vertical jump test. Specific dribble test times improved significantly in the creatine group (13.0 ± 1.5 vs. 10.2 ± 1.8 s; p < .05) after supplementation protocol. Sprint-power test times were significantly improved after creatine-monohydrate supplementation (2.7 ± 0.4 vs. 2.2 ± 0.5 s; p < .05) as well as vertical jump height (49.2 ± 5.9 vs. 55.1 ± 6.3 cm; p < .05) in creatine trial. Furthermore, dribble and power test times, along with vertical jump height, were superior in creatine versus placebo trial (p < .05) at post-supplementation performance. There were no changes in specific endurance test results within or between trials (p > .05). There were no between-trial differences in the placebo trial (p > .05). The main finding of the present study indicates that supplementation with creatine in young soccer players improved soccer-specific skill performance compared with ingestion of placebo.